2023
DOI: 10.1002/adma.202304738
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Bioprinting for Wound Healing

Abstract: Bioprinting has attracted much attention due to its suitability for fabricating biomedical devices. In particular, bioprinting has become one of the growing centres in the field of wound healing, with various types of bioprinted devices being developed, including 3D scaffolds, microneedle patches and flexible electronics. Bioprinted devices can be designed with specific biostructures and biofunctions that closely match the shape of wound sites and accelerate the regeneration of skin through various approaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 199 publications
0
11
0
Order By: Relevance
“…3D bioprinting uses a computer-controlled 3D printer to precisely deposit bioinks composed of living cells and biomaterials in a layer-by-layer manner to reconstruct the normal skin macro structure and microscopic features, making it biologically active. [11][12][13] Recent advances in 3D skin bioprinting indicate a brighter future for its application. Of note, these new developments will bring new opportunities for the application of 3D skin bioprinting technology in the treatment of radiation-associated skin injuries.…”
Section: Advancements In 3d Skin Bioprintingmentioning
confidence: 99%
See 2 more Smart Citations
“…3D bioprinting uses a computer-controlled 3D printer to precisely deposit bioinks composed of living cells and biomaterials in a layer-by-layer manner to reconstruct the normal skin macro structure and microscopic features, making it biologically active. [11][12][13] Recent advances in 3D skin bioprinting indicate a brighter future for its application. Of note, these new developments will bring new opportunities for the application of 3D skin bioprinting technology in the treatment of radiation-associated skin injuries.…”
Section: Advancements In 3d Skin Bioprintingmentioning
confidence: 99%
“…Previously, three-dimensional (3D) bioprinting as one innovative and cutting-edge life science technology is emerging. 11,12 What is more, the experimental studies for 3D bioprinting skin substitutes treating a variety of skin injuries have been reported. [12][13][14] However, the applications of 3D bioprinting skin in treating radiation-associated skin injuries have not yet been addressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that 4D-printed biomaterials can successfully guide stem cell differentiation and fate [ 92 ]. The potential applications of 4D-printed biomaterials include regeneration in craniofacial skeletal muscle [ 93 ], wound healing [ 94 ], implants for bladder disorders [ 95 ], and in vitro models of fibroblast remodeling [ 96 ].…”
Section: 3d Cell Culturesmentioning
confidence: 99%
“…The skin is the largest organ in humans and serves as a physical barrier, mediates immune defense and thermoregulation, and acts as a tactile sensor 117 , 118 . Wound healing is a complex process that involves inflammation, cell migration, proliferation, and tissue remodeling 57 , 61 , 118 .…”
Section: Applications Of Exosome-loaded Biomaterialsmentioning
confidence: 99%